SUATU KAJIAN PERBANDINGAN PENGATURAN TINDAK PIDANA PENGHINAAN TUHAN (BLASPHEMY) DI INDONESIA DAN DI BERBAGAI NEGARA ASING - Loso . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Defamation  offense  against  God  (blasphemy)  of  the  Criminal  Code  has  not  been  set  explicitly, however, for the implementation of the actions that occur can be constructed in Article 156 and Article 156a of the Criminal Code. But the concept of the 2012 Criminal Code offense of contempt of  God  (Blasphemy)  has  set  out  clear.  In  some  foreign  countries  there  are  clearly  formulate Blasphemy in its penal code (as in the Netherlands, Finland), but also there are not formulating defamation  offense  against  God  (blasphemy)  explicitly,  as  in  Belgium,  Brunei  Darussalam, however  blasphemous  offense  can  still  criminalized  through  article  humiliation  /  desecration  of religious life. Keywords: crime, blasphemy.